Set Shifting and Inhibition Deficits as Potential Endophenotypes for Depression. (June 2021) - Liu, Huiting; Funkhouser, Carter J.; Langenecker, Scott A.; Shankman, Stewart A.
Highlights: Endophenotypes, or intermediate etiological processes, may be potential therapeutic targets. Examined set-shifting and/or inhibitions deficits as potential endophenotypes for depression. Set-shifting was familial and impaired in both current and remitted depression. Set-shifting deficits in remitted depression were not due to comorbid disorders. Inhibition was familial, but was generally not impaired in current or remitted MDD. Abstract: The etiology of Major Depressive Disorder (MDD) is poorly understood, and identifying endophenotypes, or intermediate processes implicated in pathophysiology, for MDD may inform treatment and identification/prevention efforts. Impaired set-shifting and inhibition are commonly observed in MDD; however, few studies have examined they are endophenotypes for MDD. Thus, the present study tested whether set-shifting and/or inhibition satisfy several endophenotype criteria: specifically, whether they were (1) impaired in current MDD, (2) impaired in remitted MDD, and (3) familial (i.e., correlated within sibling pairs). Set-shifting and inhibition were assessed using subtests from the Delis-Kaplan Executive Function System. Psychopathology was assessed using the Structured Clinical Interview for DSM-5. Results indicated set-shifting deficits were familial and present in both current MDD and in remitted MDD individuals who had no current disorders, suggesting they may be state-independent. Inhibition was familial, but was generally not impaired in current nor remitted MDD (although the remitted MDD group with no current disorders exhibited impairments on one of the two inhibition tasks). These findings indicate that impaired set-shifting is a promising endophenotype candidate for MDD. Findings are limited to young adults, and further research is needed to test generalizability to other populations, evaluate longitudinal relationships, and examine other endophenotype criteria.